Comparison of the Effects of Using Physiological Methods and Accompanying a Doula in Deliveries on Nulliparous Women's Anxiety and Pain: A Case Study in Iran. Issue 4 (October 2017) - Ravangard, Ramin; Basiri, Aliye; Sajjadnia, Zahra; Shokrpour, Nasrin
Abstract : Childbirth is a great moment in a woman's life and is inevitably influenced by emotional, social, and psychological stress. This study aimed to assess the anxiety and pain level of nulliparous women giving birth using physiological methods (without doula support) during labor and those women supported by a doula at Towhid Hospital of Jam, Bushehr, Iran in 2015. In this interventional study, 150 women were randomly assigned to either an intervention (with doula support) or a control group (with no doula support). The intrapartum, postpartum, and hidden anxiety levels were measured using Spielberger standard questionnaire used for assessing anxiety. The labor pain rate was evaluated using McGill questionnaire. Results showed that the average rate of obvious anxiety during labor was 57.76 ± 9.57 in physiological delivery (without doula) and 48.04 ± 9.61 in doula-supported delivery. The difference between mean scores of obvious anxiety during labor was significant. The mean anxiety of the control group (who did not receive doula support) was higher ( P = .000). Also, the difference between the mean labor pain scores of the 2 groups was statistically significant. The results of the study showed that doula's presence has positive significant effects on labor pain and anxiety reduction; also, doula-supported mothers reported considerably lower pain and anxiety compared with those experiencing physiological delivery (without doula). Thus, the increased use of doula in hospitals all over the country is recommended.